Determinasi Profitabilitas Perusahaan Batu Bara: Peran Working Capital Turnover, Likuiditas, dan Struktur Modal - Aulia Rahman; Wiwin Aminah (Politeknik Ganesha Medan, 2026)
This study examines the effects of working capital turnover, liquidity, also capital structure on the profitability of coal industry corporations listed on the IDX during 2021-2024. Previous studies have produced mixed findings and provided limited empirical evidence, particularly in the coal industry. Profitability, as a crucial metric of financial performance, may be influenced by how effectively companies manage working capital, liquidity, and determine their financing structure. In addition, Challenges facing the coal business include price volatility also regulatory changes that might affect profitability. All coal-related businesses that were listed on the IDX throughout the study period make up the population. Purposive sampling was used to choose 29 businesses, yielding 116 firm-year observations from companies that consistently published annual reports between 2021 and 2024. This investigation uses a quantitative methodology also secondary data from official IDX publications also yearly reports. Panel data regression using EViews 13 was used to examine the data after traditional assumption testing. The findings show that capital structure, liquidity, and working capital turnover simultaneously affect profitability at the same time. While working capital turnover and liquidity have little bearing on profitability, capital structure has a somewhat negative impact. These results imply that higher capital structure levels may reduce profitability. This research enriches the literature by offering updated empirical findings and emphasizing capital structure as a key determinant of profitability in the coal industry.